Identification of Factors Causing Household Food Waste in Sidoarjo: Identifikasi Faktor Penyebab Food Waste Rumah Tangga Di Sidoarjo - Cahyana, Atikha Sidhi; Hidayat, Abdul Rakhmad; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2022)
Every household produces food waste. Based on data from the DKLH Sidoarjo (2021), the people of Sidoarjo produce 2,400 tons of household waste everyday. Although 116 TPST have been provided, only 600tons of waste per day can be managed properly. Most of the waste consists of leftover food and vegetables from household waste. Therefore, this study aims to determine the factors that influence the emergence of food waste so that it affects the pile of garbage in Sidoarjo. The method used is a dynamic system. System dynamics can help to find the couse and effect of the main problem widely because System dynamics is a method used to describe, model, and simulate a dynamic system (over time and changing). Yhe research area that examines the incidence of household food waste is carried out at the Gedangan TPS. In Gedangan TPS, there are 3 areas that affect the emergence of food waste, namely Gedangan Village, Calukan Hamlet RW 5, Congkop RW 2. The area selection in Gedangan Village is due to the number of households that are more than other Sidoarjo areas and in a day food waste enters the area. TPS Gedangan as much as 2,014 Kg. All food waste in the Gedangan TPS is immediately disposed of the Jabon TPA without processing it first. The results of this study that the most influential factors are population, number of deaths, urbanization, cooking process, people’s culture of disposing planning, inventory planning, serving portions.